Proactive Advising for University Students with Disabilities in the Global South: Applying Basic Counseling Responses - Akande, Abigail (Indonesian Journal of Disability Studies, 2023)
From the framework of the proactive or intrusive advising approach, this paper presents a plausible method for addressing the academic and social issues stemming from being a university student with a disability and living in an under-resourced country. This paper will 1) address the necessity of support services for students with disabilities on university campuses in the Global South; 2) present proactive advising as a mechanism for university student advocacy and support at universities in the Global South; 3) highlight policy obligations of the Convention on the Rights of Persons with Disabilities (CRPD) regarding the education of students with disabilities; and 4) introduce basic counseling responses as a culturally appropriate approach for university professionals to build rapport, actively engage, and promote reflection with students with disabilities in their pursuits of optimal academic achievement. Recommendations will be provided for sustainable top-down and bottom-up approaches for student support and faculty development.